2017
DOI: 10.1002/term.2609
|View full text |Cite
|
Sign up to set email alerts
|

3D matrix‐embedding inhibits cycloheximide‐mediated sensitization to TNF‐alpha‐induced apoptosis of human endothelial cells

Abstract: The programmed form of cell death (apoptosis) is essential for normal development of multicellular organisms. Dysregulation of apoptosis has been linked with embryonal death and is involved in the pathophysiology of various diseases. Others and we previously demonstrated endothelial biology being intertwined with biochemical and structural composition of the subendothelial basement membrane. We now demonstrate that a three-dimensional growing environment significantly shields endothelial cells from cytokine-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Genes that were upregulated in 3D ECs relative to those of ECs cultured in 2D TCPs were enriched within the GO BP categories vasculature development, cardiovascular system development, and regulation of cell proliferation. In addition, the GO BP terms 'the integrin-mediated signalling pathway' and 'cell surface receptor signalling pathway' , and the GO MF terms 'integrin binding' , 'collagen binding involved in cell-matrix adhesion' and 'ECM binding' were enriched, which was proven in a recent study showing that 3D matrix-embedded ECs exhibit altered integrin expression and express significantly reduced phosphorylated focal adhesion kinase compared with those of ECs cultured on 2D TCPs [27]. Zhang et al also reported that ECs cultured on TCPs adopt a proliferative phenotype compared with ECs cultured on top of or encapsulated in PEG hydrogels and gelled Matrigel, which was related to the BP term 'regulation of cell proliferation' that was enriched in our results [8].…”
Section: Discussionmentioning
confidence: 81%
“…Genes that were upregulated in 3D ECs relative to those of ECs cultured in 2D TCPs were enriched within the GO BP categories vasculature development, cardiovascular system development, and regulation of cell proliferation. In addition, the GO BP terms 'the integrin-mediated signalling pathway' and 'cell surface receptor signalling pathway' , and the GO MF terms 'integrin binding' , 'collagen binding involved in cell-matrix adhesion' and 'ECM binding' were enriched, which was proven in a recent study showing that 3D matrix-embedded ECs exhibit altered integrin expression and express significantly reduced phosphorylated focal adhesion kinase compared with those of ECs cultured on 2D TCPs [27]. Zhang et al also reported that ECs cultured on TCPs adopt a proliferative phenotype compared with ECs cultured on top of or encapsulated in PEG hydrogels and gelled Matrigel, which was related to the BP term 'regulation of cell proliferation' that was enriched in our results [8].…”
Section: Discussionmentioning
confidence: 81%
“…An immunoprecipitation kit (Invitrogen) was used to quantify association of receptorinteracting protein (RIP) with focal adhesion kinase (FAK). Immunoprecipitation and Western blot analysis were performed as previously described (52). Antibody specifications are outlined in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Composition of the subendothelial extracellular matrix undergoes several important changes during evolution of atherosclerosis (31,48). In addition we recently demonstrated that the spatial formation of the tissue environment impacts proneness of ECs to undergo apoptosis with a three-dimensional environment exerting protection over a two-dimensional environment (52).…”
Section: Introductionmentioning
confidence: 96%
“…Endothelial dysfunction is an important contributor to atherosclerosis [1]. Zanotelli et al found that ECs can maintain good activity and form a capillary-like network when embedded in a polyethylene glycol hydrogel for 3D culture, which allow for better evaluation of the morphogenesis of vascular ECs [11] In recent years, Saemisch et al used microarray chips to detect significant differences in the expression of integrins α1, α2, β3, and other subunits in human aortic ECs cultured in three dimensions, which are also related to cytoskeleton, migration, adhesion, and matrix remodelling [12]. The above studies indicate that the biological characteristics and functions of ECs may change owing to the 3D culture environment, and the changes in EC functions in 3D culture may be related to the differential expression of these genes.…”
Section: Introductionmentioning
confidence: 99%